Salicylic Acid-Regulated Antioxidant Mechanisms and Gene Expression Enhance Rosemary Performance under Saline Conditions - El-Esawi, Mohamed A.; Elansary, Hosam O.; El-Shanhorey, Nader A.; Abdel-Hamid, Amal M. E.; Ali, Hayssam M.; Elshikh, Mohamed S. (Frontiers in Physiology, 2017)
Salinity stress as a major agricultural limiting factor may influence the chemical composition and bioactivity of Rosmarinus officinallis L. essential oils and leaf extracts. The application of salicylic acid (SA) hormone may alleviate salinity stress by modifying the chemical composition, gene expression and bioactivity of plant secondary metabolites. In this study, SA was applied to enhance salinity tolerance in R. officinallis. R. officinallis plants were subjected to saline water every two days (640, 2000 and 4000 ppm NaCl) and 4 biweekly sprays of SA at 0,100, 200 and 300 ppm for 8 weeks. Simulated salinity reduced all vegetative growth parameters such as plant height, plant branches and fresh and dry weights. However, SA treatments significantly enhanced these plant growth and morphological traits under salinity stress. Salinity affected specific major essential oils components causing reductions in α-pinene, β-pinene and cineole along with sharp increases in linalool, camphor, borneol and verbenone. SA applications at 100-300 ppm largely reversed the effects of salinity. Interestingly, SA treatments mitigated salinity stress effects by increasing the total phenolic, chlorophyll, carbohydrates and proline contents of leaves along with decline in sodium and chloride. Importantly, this study also proved that SA may stimulate the antioxidant enzymatic mechanism pathway including catalase (CAT), superoxide dismutase (SOD) and ascorbate peroxidase (APX) as well as increasing the non-enzymatic antioxidants such as free and total ascorbate in plants subjected to salinity. Quantitative real-time PCR analysis revealed that APX and 3 SOD genes showed higher levels in SA-treated rosemary under salinity stress, when compared to non-sprayed plants. Moreover, the expression level of selected genes conferring tolerance to salinity (bZIP62, DREB2, ERF3 and OLPb) were enhanced in SA-treated rosemary under salt stress, indicating that SA treatment resulted in the modulation of such genes expression which in turn enhanced rosemary tolerance to salinity stress.